Biomass accumulation-influencing factors in microalgae farms - Gerson O. L. Pedruzi; Matheus L. Amorim; Raquel R. Santos; Márcio A. Martins; Marcelo G. M. V. Vaz (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Due to the emergence of large microalgae farms and increased competition in this sector, the search for higher productivity is common. One way to achieve this goal in microalgae production is to optimize the factors that influence their growth during the cultivation stage to increase the accumulation of bio-compounds of interest. In this stage, the factors that most influence are: nutrition, gas diffusion, light intensity and quality and, finally, stirring, which directly affects all other factors. Thus, a review and an evaluation of the influence and importance of stirring were performed in the present study. The nutrients that most influence biomass accumulation are carbon, nitrogen and phosphorus, but their proportion is directly related to the proposed objective for microalgae. In the diffusion of gases, it is essential to supply adequate CO2 for the growth of microalgae, and flue gases can be used. Also, it is necessary to ensure proper removal of photosynthetic O2, which could inhibit microalgae metabolism and slow their growth rate. It is important to provide the appropriate light intensity for photosynthesis, but excess may cause photoinhibition in cultivation. Stirring is of paramount importance to ensure nutrient distribution in the medium, gas diffusion (incorporation of CO2 and removal of O2) and adequate exposure of microalgae to light, reducing the effects of photoinhibition and self-shading.